2022
DOI: 10.1039/d1nr06204b
|View full text |Cite
|
Sign up to set email alerts
|

Dipole moment and pressure dependent interlayer excitons in MoSSe/WSSe heterostructures

Abstract: The broken mirror symmetry of the two-dimensional (2D) Janus material brings novel quantum properties and various application prospects. Particularly, when stacking into heterostructure, its intrinsic dipole moments and large band...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…[18][19][20] It has been found that the 2D MoSSe-based vdWHs exhibit exciting novel properties under the influence of the intrinsic electric field of MoSSe. [21][22][23][24] Compared with monolayer MoSSe, multilayer MoSSe has a larger dipole and higher carrier mobility, which are suitable for electronic devices and photocatalysis applications. 25 The charge transfer between MoSSe and other layers leads to the generation of a built-in electric field, which can effectively promote the separation of photogenerated electrons and holes, making it suitable for photocatalytic and photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] It has been found that the 2D MoSSe-based vdWHs exhibit exciting novel properties under the influence of the intrinsic electric field of MoSSe. [21][22][23][24] Compared with monolayer MoSSe, multilayer MoSSe has a larger dipole and higher carrier mobility, which are suitable for electronic devices and photocatalysis applications. 25 The charge transfer between MoSSe and other layers leads to the generation of a built-in electric field, which can effectively promote the separation of photogenerated electrons and holes, making it suitable for photocatalytic and photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional Janus TMDs have recently attracted a great deal of attention due to their appealing properties and potential applications in devices. These materials, especially when stacked into heterostructures, are highly advantageous for the photoexcitation features of electron–hole pairs, or excitons, due to their intrinsic out-of-plane dipole moment and significant band shift. ,,, To align type-II bands to form interlayer excitons (IXs), single-layer composition and stacking sequence have been selected to construct van der Waals (vdW) heterostructures out of distinct 2D materials. ,, Meanwhile, when light is absorbed, the weak dielectric screening of two-dimensional semiconductors enables the creation of tightly bound excitons, resulting in exceptional optical characteristics like layer-dependent exciton modulation and discrete excitonic peaks with significant photoluminescence response . The heterostructures, including Janus TMDs, maintain the original performance of a single-layer TMDC while adding an electric field, which significantly enhances the interaction of the photoexcited electron and hole.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,17,20 To align type-II bands to form interlayer excitons (IXs), single-layer composition and stacking sequence have been selected to construct van der Waals (vdW) heterostructures out of distinct 2D materials. 17,19,20 Meanwhile, when light is absorbed, the weak dielectric screening of two-dimensional semiconductors enables the creation of tightly bound excitons, 19−22 resulting in exceptional optical characteristics like layer-dependent exciton modulation and discrete excitonic peaks with significant photoluminescence response. 21 The heterostructures, including Janus TMDs, maintain the original performance of a singlelayer TMDC while adding an electric field, which significantly enhances the interaction of the photoexcited electron and hole.…”
Section: Introductionmentioning
confidence: 99%
“…33 Besides, the latest GW + BSE investigation reported by Pang et al indicated that the photoexcited properties of the interlayer excitons with a long lifetime in MoSSe/WSSe heterostructure can be greatly modulated by the parallel-arranged intrinsic dipole moments and the hydrostatic pressure. 34 In general, through adjusting the stacking pattern, 35 the applied electric field 36 and the twist angle between crystal axes, 37,38 the interfacial coupling effect of vdW heterojunctions can be manipulated to affect their quantum transport, polarization excitation and electrochemical properties. It is intuitively believed that the charge transfer dynamics in a heterostructure is strongly dependent on the interlayer interaction or stacking pattern, because charge transfer can be understood as through the overlap of electronic states resulting from interlayer coupling.…”
Section: Introductionmentioning
confidence: 99%
“…33 Besides, the latest GW + BSE investigation reported by Pang et al indicated that the photoexcited properties of the interlayer excitons with a long lifetime in MoSSe/WSSe heterostructure can be greatly modulated by the parallel-arranged intrinsic dipole moments and the hydrostatic pressure. 34…”
Section: Introductionmentioning
confidence: 99%